Psychological support in end-of-life decision-making in neonatal intensive care units: Full population survey among neonatologists and neonatal nurses. (March 2020) - Dombrecht, Laure; Cohen, Joachim; Cools, Filip; Deliens, Luc; Goossens, Linde; Naulaers, Gunnar; Beernaert, Kim; Chambaere, Kenneth
Background: Moral distress and burnout related to end-of-life decisions in neonates is common in neonatologists and nurses working in neonatal intensive care units. Attention to their emotional burden and psychological support in research is lacking. Aim: To evaluate perceived psychological support in relation to end-of-life decisions of neonatologists and nurses working in Flemish neonatal intensive care units and to analyse whether or not this support is sufficient. Design/participants: A self-administered questionnaire was sent to all neonatologists and neonatal nurses of all eight Flemish neonatal intensive care units (Belgium) in May 2017. The response rate was 63% (52/83) for neonatologists and 46% (250/527) for nurses. Respondents indicated their level of agreement (5-point Likert-type scale) with seven statements regarding psychological support. Results: About 70% of neonatologists and nurses reported experiencing more stress than normal when confronted with an end-of-life decision; 86% of neonatologists feel supported by their colleagues when they make end-of-life decisions, 45% of nurses feel that the treating physician listens to their opinion when end-of-life decisions are made. About 60% of both neonatologists and nurses would like more psychological support offered by their department when confronted with end-of-life decisions, and 41% of neonatologists and 50% of nurses stated they did not have enough psychological support from their department when a patient died. Demographic groups did not differ in terms of perceived lack of sufficient support. Conclusion: Even though neonatal intensive care unit colleagues generally support each other in difficult end-of-life decisions, the psychological support provided by their department is currently not sufficient. Professional ad hoc counselling or standard debriefings could substantially improve this perceived lack of support.